Experimental Study on Extraction of Aluminum and Iron from Bayer Red Mud by Deep Reduction Sintering - Ruiming He; Yong Wang; Aimin Li; Wei Shi; Yajun Xu; Yulian Zhao (Kuangchan zonghe liyong, 2022)
The presence of iron and aluminum in the red mud affect the leaching and extraction of scandium and rare earths. Through the analysis and testing of the Bayer process red mud, a technical plan for the reduction and sintering to recover aluminum and iron was designed, and the process of the molten deep reduction and sintering to extract aluminum and iron from the red mud was systematically studied. Under the optimum conditions, the grade of iron concentrate is 73.97%, the recovery rate is 90.27%, and the dissolution rate of aluminum is 96.28%, the aluminosilicate mineral is converted into sodium aluminate, and the sodium aluminate solution is obtained by alkali leaching, which can be used to prepare polyaluminum chloride products in the subsequent. The iron-containing complex minerals in the red mud are transformed into magnetic magnetite and elemental iron, and the iron-containing minerals are recovered by magnetic separation to realize the coordinated recovery of iron and aluminum in the red mud. The process not only weakens the adverse effect of aluminum and iron ore on the subsequent extraction of scandium, titanium and rare earth by acid leaching, but also enriches titanium, scandium and rare earth in the tailings, which is conducive to the realization of multi-element comprehensive utilization of red mud.